Faktor-faktor yang mempengaruhi permintaan masyarakat terhadap jasa rahn pada Pegadaian Syariah Singkawang - B01111049, Fidia Wulansari (Jurnal Curvanomic, 2015)
The title of this research is â€œFactors that influencepeopleâ€™s demand for rahn service satthe Sharia pawnshopin Singkawangâ€. Theresearch aimed to analyze the factors that influence the peopleâ€™s demand for rahnservicesat the Sharia pawnshop Alianyang Dalam in Singkawang Branch. The research menthond is qualitative descriptive with primery and secondary data. The process of data collecting is done with observation, interview and questionaire and literature. The respondent of this research is people of the respondent 60 people of cunsument from Sharia pawnshop Alianyang Dalam in Singkawang Branch. The result of the research shows that there are 4 factors that influence the society request to rahm service. Those factors are security factor with the highest answer from respondent are very agree. Ujroh factor with the highest answer from respondent are very agree. Service factor with most of the respondent answered agree. Trust factor with most of respondent answered agree. Â Keywords: the trust factor, security, service, ujroh, and rahn service